Предпринимательство как явление экономического развития общества (Путеводитель предпринимателя, 2020)
In clause the basic theoretical sights, within the limits of the economic theory, on concepts «business» and «businessman» are systematized and stated, knowledge about which it is necessary in modern social and economic conditions.